Molecular basis of alpha thalassemia among aborigines in Kelantan - Rusli, Nurul Atikah (Universiti Sains Malaysia, 2016)
Alpha thalassemia is a common inherited disorder of hemoglobin (Hb) synthesis throughout all tropical and subtropical regions of the world. It is normally results from deletion of one or both alpha genes at chromosomes 16pl 3.3. Carriers of these genes have a variable degree of anemia (low Hb), decreased mean corpuscular hemoglobin (MCH/pg), decreased mean corpuscular volume (MCV/fl) and a normal or slightly decreased level of HbA2. Nevertheless, molecular analysis is essential to support these hematological observations. Thus, we presented a cross-sectional study to screen for the deletional defects in the a-globin gene cluster among aborigines population in Gua Musang, Kelantan. Deletion of alpha genes was identified by single-tube multiplex-Polymerase Chain Reaction (PCR) method and 1% agarose gel electrophoresis. Deletion mutations include single gene deletions -a3.7 and -a4.2, double gene deletions —SEA and —THAI in 52 blood samples from studied respondents. The results revealed two out of 52 respondents had alpha gene deletion, one respondent with (1.9%) single gene deletion of-a3.7 and one respondent with (1.9%) double deletion of —SEA. In conclusion, this study will helps in determining the alpha thalassemia status among aborigines for their future health planning and management.